Criminal behavior and contingency - Lee, Chang-Moo (Frontiers in Psychology, 2023)
Although their perspectives and approaches vary, existing criminological theories are all based on the deterministic optimism that the crucial causes of criminal behavior must exist and can be uncovered. However, no key factor can fully explain the causes of criminal behavior. All factors that directly affect the occurrence of criminal behavior are important, and contingency is always at work. More feasible crime prevention and control measures can be proposed only considering the contingency factor. The aim of this study is to point out the limitations of the deterministic view of existing criminological theories that explain the causes of crime after knowing the results, and simultaneously to propose the contingency model with viable alternative solutions.